2013
DOI: 10.1007/s10989-013-9366-8
|View full text |Cite
|
Sign up to set email alerts
|

Some Mechanistic Aspects on Fmoc Solid Phase Peptide Synthesis

Abstract: Peptides are biomolecules that may have several biological activities which makes them important to the environment in which they operate. Sometimes it is necessary for larger amounts of peptides to carry out some studies, like biological tests, NMR structural research or even interaction studies between peptides with other molecules. Expression can be an alternative for that. However, synthesis is specially useful when unnatural modifications or introduction of site specific tags are required. Synthetic pepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
10

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 74 publications
0
15
0
10
Order By: Relevance
“…Using the manual solid-phase Fmoc method, PI (sequence, CASPSGALRSC) ( 18 ) was synthesized to determine whether the phage-coating protein was required for internalization into target cells. For cellular localization, the synthesized peptide was labeled with FITC at the N-terminus of PI (designated PI-FITC).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the manual solid-phase Fmoc method, PI (sequence, CASPSGALRSC) ( 18 ) was synthesized to determine whether the phage-coating protein was required for internalization into target cells. For cellular localization, the synthesized peptide was labeled with FITC at the N-terminus of PI (designated PI-FITC).…”
Section: Methodsmentioning
confidence: 99%
“…The association of the specific internalization of the peptide into MDA-MB-231 cells with macropinocytosis and caveolin- and clathrin-mediated endocytosis was investigated. Our previous study found that a lung cancer cell line, Calu-1, also demonstrated an affinity for the peptide, similarly to the human breast cancer cell line MDA-MB-231 ( 18 ); thus, the present study investigated the hypothesis that major histocompatibility complex class I (MHC-I) antigen molecules and the cytomembrane proteins of these two cell lines may also be candidate proteins that are involved in the process of transmembrane transduction of PI. MHC-I antigen-mediated transmembrane transduction was investigated, and the membrane proteins of MDA-MB-231 and Calu-1 were extracted and compared by two-dimensional (2-D) electrophoresis ( 19 ) to identify those that were common to both cell lines and may be involved in the process of transmembrane transduction of PI.…”
Section: Introductionmentioning
confidence: 98%
“…These reactions work better in an electron donor and relative polar medium (DMF or N-methylpirrolidone [NMP]) compared to a relatively non-polar one (dichloromethane [DCM]) [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Fmoc group removal in solid phase peptide synthesis (SPPS) proceeds through a two-step mechanism: the removal of the acidic proton at the 9-position of the fluorene ring system by a mild base, preferably a secondary amine, and the subsequent β-elimination that yields a highly reactive dibenzofulvene (DBF) intermediate which is immediately trapped by the secondary amine to form stable adducts (Scheme 1). These reactions work better in an electron donor and relative polar medium (DMF or N-methylpirrolidone [NMP]) compared to a relatively non-polar one (dichloromethane [DCM]) [6,7]. Scheme 1.…”
Section: Introductionmentioning
confidence: 99%
“…Chemical structure of Cibacron blue[28]. Chemical structure of the rink-amide resin used in the SPPS[29].…”
mentioning
confidence: 99%